2020
DOI: 10.1108/jsm-05-2020-0199
|View full text |Cite
|
Sign up to set email alerts
|

Customer brand engagement during service lockdown

Abstract: Purpose While the customer brand engagement (CBE) research has advanced important insight, most studies to date explore CBE under regular, free-market conditions, yielding an important knowledge gap regarding its manifestation under less regular conditions, including disaster/pandemics. This study, therefore, aims to explore CBE with essential/non-essential service during COVID-19-prompted citizen lockdown. Design/methodology/approach Based on a review, the authors develop a framework of lockdown-based CBE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 67 publications
2
64
0
Order By: Relevance
“…Based on our results, we thus suggest tourism marketers/managers to develop differing marketing tactics/strategies that underline the role of fear of COVID-19, perceived risk, and their effects on attitude/CBE during pandemic. For example, to cater prospective tourists in pandemic, managers are suggested to sustain/develop various service interaction platforms (Ebrahimi et al, 2020;Harrigan et al, 2017;Narangajavana et al, 2017), including mobile apps, e-commerce websites, virtual reality/VR-based touch-points or brand communities (Hollebeek et al, 2020;Yu et al, 2020), that are helpful in engaging such customers. Further, during COVID-19 pandemic, tourism/travel industry has to be vigilant and prioritize health/safety-related issues (Bae & Chang, 2020).…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Based on our results, we thus suggest tourism marketers/managers to develop differing marketing tactics/strategies that underline the role of fear of COVID-19, perceived risk, and their effects on attitude/CBE during pandemic. For example, to cater prospective tourists in pandemic, managers are suggested to sustain/develop various service interaction platforms (Ebrahimi et al, 2020;Harrigan et al, 2017;Narangajavana et al, 2017), including mobile apps, e-commerce websites, virtual reality/VR-based touch-points or brand communities (Hollebeek et al, 2020;Yu et al, 2020), that are helpful in engaging such customers. Further, during COVID-19 pandemic, tourism/travel industry has to be vigilant and prioritize health/safety-related issues (Bae & Chang, 2020).…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…This cluster is expected to face a stimulating future, given the pace of new (e.g., technology-driven) methodological advances, whether through big data-, neuro-tracking-, artificial intelligence-, augmented/virtual/mixed reality-, the Internet-of-Everything-, or quantum-or edge-computing developments, to name a few, thus facilitating CE's measurement, -monitoring, -cultivation, -design, or -dissolution, as required (e.g., Kunz et al, 2017;Bridger, 2017). Particularly in COVID-19-impacted marketplaces, these technologydriven methodological advances, many of which can be adopted during pandemic-imposed restrictions (e.g., social distancing/lockdown; Hollebeek et al, 2020c) The second theme, Online CE, centers on CE with brands, as facilitated by digital platforms (e.g., Heller et al, 2021;Tuškej and Podnar, 2018;Harrigan et al, 2018). This cluster is also expected to see a dynamic future.…”
Section: Further Researchmentioning
confidence: 99%
“…The third theme of CE's Value-Co-creating Capacity highlights CE's capacity to yield cocreated or codestroyed value (e.g., Bowden et al, 2017;Merrilees, 2016), as noted, which can transpire through face-to-face or (e.g., pandemic-imposed) physically distant interactions (e.g., Ramaswamy and Ozcan, 2016;Hollebeek et al, 2020c). For example, as singletons initially remain distanced from their potential match in online dating, their fate is bound by the other's assessment of them (e.g., "swipe left/right"), even though they are yet to meet in person.…”
Section: Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A study found that the customers' desires would transfer from stockpiling goods to the high-quality buying experiences (eg, face-toface interactions) in times of lockdown. 25 Travel needs contributed to the recent resurgence of many outbreaks in different parts of China, particularly when there are management loopholes in the airport and at the scenic spots. [26][27][28][29] For the social connectedness, although long-term social distancing has boosted the advancement of digital technology in online work and life, there are still groups of people like elderly offline and professionals becoming much busier than ever should not be forgotten.…”
Section: Introductionmentioning
confidence: 99%